Synthesis, spectroscopic studies and biological activities of acylthiourea derivatives as potential anti-bacteria agents - - Wan M. Khairul, Ahmad Ariffin Aziah, Ismail Noraznawati, Daud Adibah Izzati, (Universiti Pendidikan Sultan Idris, 2016)
Synthesis, spectroscopic studies and biological activities of acylthiourea derivatives as potential anti-bacteria agents by - Wan M. Khairul, Ahmad Ariffin Aziah, Ismail Noraznawati, Daud Adibah Izzati,